Prva pomoč: Navodila za vaje za študente medicine (University of Maribor Press, 2019)
First Aid: Instructions for Tutorials for Medical Students. The study material »First Aid: Instructions for Tutorials for Medical Students« represents all basic contents of giving first aid which a medical student should be acquainted with and know how to use them also in practice. The publication is an aid for theoretical preparation for the performance of practical drills in learning procedures of first aid and in usage of substances and aids which are used in first aid. According to valid guidelines of the European Resuscitation Council or their Slovenian translation various procedures of first aid giving are dealt with in chapters: from basic resuscitation procedures of adults and children, bandaging wounds, immobilization, usage of automatic and semi-automatic defibrillator to removal of a foreign object and release of airway, introduction of respiratory tube and treatment of injured persons. The text of the protocol of first aid giving is supplemented by illustrative photographs and sketches of procedures and that is why the study material facilitates acquisition of theoretical and practical knowledge to a student for giving first aid to patients and injured persons. 1st reprint of 1. edition: 24. 06. 2022 2nd reprint of 1. edition: 24. 06. 2024